Chemical compositions of essential oils of Amomum verum and Cinnamomum parthenoxylon and their in vitro biological properties - Janpen Tangjitjaroenkun; Rungnapa Tangchitcharoenkhul; Waraporn Yahayo; Suangson Supabphol; Ruengrit Sappapan; Roongtawan Supabphol (Shahrekord University of Medical Sciences, 2020)
Introduction: In eastern Thailand, Amomum verum and Cinnamomum parthenoxylon are native plants used by local communities for their medical and culinary properties. This study determined the chemical composition and biological activities of the essential oils from A. verum shoots (AVSEO) and C. parthenoxylon wood (CPW-EO). Methods: Essential oils were extracted using hydro-distillation and analyzed using gas chromatography-mass spectroscopy (GC-MS). The antimicrobial activity was evaluated using the disc diffusion method and broth microdilution assay. The cytotoxic activity of the essential oils was assessed against the human prostate adenocarcinoma (DU145) cell line using 3-(4,5-dimethylthiazol2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The antioxidant activity of the essential oils was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2'-azino-bis-(3-ethylbenzothiazoline6-sulfonic acid) (ABTS) radical scavenging assays. The expression of antioxidant genes in the DU145 cells was evaluated using quantitative real-time polymerase chain reaction (qRT-PCR). Results: 1,8-Cineole was the main component in AVS-EO and CPW-EO with 84.38, and 45.65 %, respectively. AVS-EO had stronger antimicrobial activity than CPW-EO. The lowest minimum inhibitory concentration (MIC) and minimum microbicidal concentration (MMC) values of AVSEO against Candida albicans were 0.3125 and 2.5 mg/mL, respectively. Both essential oils had timedependent and dose-dependent cytotoxic effects on the DU145 human prostate adenocarcinoma cells. CPW-EO had high antioxidant activity toward DPPH and ABTS radicals with IC50 values of 4.528±0.233 and 0.045±0.007 mg/mL, respectively. The two essential oils up-regulated glutathione peroxidase (GPx) and glutathione reductase (GRx) mRNA expression in the oxidative stress response of DU145 cells. Conclusion: AVS-EO and CPW-EO might be added as natural ingredients in food or dietary supplement products for the benefit of microbial and prostate cancer inhibition.